Analisis Kinerja Akustik Panel Gedek Bambu dengan Sisipan Komposit Eceng Gondok: Melati Wijayanti, Iwan yahya, Harjana, Restu Kristiani, Eki Muqowi - Melati Wijayanti, Melati Wijayanti; Iwan Yahya, Iwan Yahya; Harjana, Harjana; Restu Kristiani, Restu Kristiani; Eki Muqowi, Eki Muqowi (Jurnal Fisika dan Aplikasinya, 2025)
This paper emphasizes on the influence of structure configuration and air bank variation on the acoustic performance of bamboo gedek panel with a water hyacinth based perforated panel insertion. The investigation was conducted experimentally based on standard laboratory test procedures. The sound absorption (o) coefficient and impedance ratio was measured by using B&K impedance tube 4206 which is refer to ASTM E-1050-98, while the four microphones spectral decomposition technique was condcuted for measuring the sound transmission loss (STL). The results shows that accumulative response of perforated panel and air bank variation increase the acoustic performance of bamboo gedek panel with the o ranging from 0,5 to 0,83 in a wide frequency range above 400 Hz. The STL ranging from 30 dB to 55 dB according to sample configuration.